An overhead docking and charging station for autonomous unmanned aircraft - Lieret, Markus; Wurmer, Florens; Hofmann, Christian; Franke, Jörg (IEEE International Conference on Automation Science and Engineering, 2021)
Autonomous unmanned aircraft (UA) are currently gaining importance in various areas of application. In addition to their use in the field of surveying, inspection or fluid application, the focus is also on the transport of goods and the monitoring of factory premises. However, decisive disadvantage of commonly used UA is their short flight time, which typically ranges between approx. 10 and 45 minutes, depending on the design and payload. For the automated use of UA, it is not practical to manually change the battery between individual flights but automated solutions are required. The automated charging methods presented so far have in common that the UA approaches the landing platform vertically or at an angle from above and stands on the landing platform after completion. In this paper, we present a novel solution for the overhead charging of UA. Thereby the UA docks vertically to the charging station from below and is locked in the station. This saves floor space and allows the use of sensors attached to UA for information acquisition and environmental monitoring while charging. In addition to the charging station and the associated docking device attached to the UA, a camera-based method for localizing the charging station and for precise docking is presented. Finally, the docking and undocking process is evaluated in a series of experiments.
CRIS-Team Scopus Importer:2021-10-29